2017
DOI: 10.20473/jn.v12i1.2750
|View full text |Cite
|
Sign up to set email alerts
|

Prolanis Implementation Effective to Control Fasting Blood Sugar, HBA1C and Total Cholesterol Levels in Patients with Type 2 Diabetes

Abstract: Introduction: Diabetes mellitus (DM) is a global disease endemic and cause of 4.6 million deaths in the world. The Indonesian government and health insurance [BPJS Kesehatan] formulate a Chronic Disease Care Program [Program Pengelolaan Penyakit Kronis (PROLANIS)] for type 2 diabetes that aims to control the glycemic status and the risk factors of macro and microvascular complications. The purpose of this study was to analyse the correlation between the implementation of PROLANIS and fasting blood sugar, HbA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 2 publications
0
12
0
1
Order By: Relevance
“…The poorer, middle, richer, and richest wealth quintiles were less likely to have health insurance than poorest� The previous study stated that there was no significant association between wealth quintile and health insurance� � 41 Another study stated that the richest households were more likely to have health insurance� � 36,42,43 This could have occurred because the health insurance scheme in Indonesia is different from that of other countries� The poorest populations receive subsidized insurance to maintain and increase their health status, , 44 such as payment for health services in the emergency department, , 45 treatment for chronic illness, , 46 and treatment of the factors associated with the success of diabetes mellitus management� � 47 The poorest population's health insurance is fully paid for by the government� The other schemes are paid for by the health insurance members themselves� This scheme makes the poorest populations more likely to be listed as health insurance member, making their coverage rate higher� The ownership of private health insurance may be the reason why the wealthier are less likely to have national health insurance� A study showed that the amount of monthly income as part of wealth is related to the demand for private insurance in Indonesia� � 48 To increase the coverage of health insurance for other economic groups, the government can subsidize premiums for them� The government can work with companies to pass regulations stating that each company has an obligation to pay for insurance for its workers� This regulation can also protect the health of workers� Rural households are less likely to have health insurance� � 40,43 The primary factor determining coverage for both the subsidized and contributory schemes in Indonesia is that citizens work and are urban residents of Java or Bali� � 49 The affordability of travel to the health insurance office can be another reason for low coverage� The existence of branch offices in each city can increase the reach of insurance agencies� An increase in the number of insurance agencies can make it easier for potential participants to register for NHI� The government can support the spreading of branch offices by providing good infrastructure and communication networks like telephone and internet� The role of the government in providing infrastructure greatly affects the existence of branch offices and customer service� Those who are divorced are less likely to have health insurance� Women often lose their health insurance in the months after a divorce 50 and thus become uninsured� � 51 Divorced women are more likely to experience socioeconomic disadvantages than married women� � 52 Divorced women lose their benefits in terms of health insurance as they are dropped from their husbands' health insurance policies� They also lose their dependent payments and are unable to afford other forms of coverage� Jobless divorced woman find it difficult to pay monthly insurance premiums, so they decide to d...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The poorer, middle, richer, and richest wealth quintiles were less likely to have health insurance than poorest� The previous study stated that there was no significant association between wealth quintile and health insurance� � 41 Another study stated that the richest households were more likely to have health insurance� � 36,42,43 This could have occurred because the health insurance scheme in Indonesia is different from that of other countries� The poorest populations receive subsidized insurance to maintain and increase their health status, , 44 such as payment for health services in the emergency department, , 45 treatment for chronic illness, , 46 and treatment of the factors associated with the success of diabetes mellitus management� � 47 The poorest population's health insurance is fully paid for by the government� The other schemes are paid for by the health insurance members themselves� This scheme makes the poorest populations more likely to be listed as health insurance member, making their coverage rate higher� The ownership of private health insurance may be the reason why the wealthier are less likely to have national health insurance� A study showed that the amount of monthly income as part of wealth is related to the demand for private insurance in Indonesia� � 48 To increase the coverage of health insurance for other economic groups, the government can subsidize premiums for them� The government can work with companies to pass regulations stating that each company has an obligation to pay for insurance for its workers� This regulation can also protect the health of workers� Rural households are less likely to have health insurance� � 40,43 The primary factor determining coverage for both the subsidized and contributory schemes in Indonesia is that citizens work and are urban residents of Java or Bali� � 49 The affordability of travel to the health insurance office can be another reason for low coverage� The existence of branch offices in each city can increase the reach of insurance agencies� An increase in the number of insurance agencies can make it easier for potential participants to register for NHI� The government can support the spreading of branch offices by providing good infrastructure and communication networks like telephone and internet� The role of the government in providing infrastructure greatly affects the existence of branch offices and customer service� Those who are divorced are less likely to have health insurance� Women often lose their health insurance in the months after a divorce 50 and thus become uninsured� � 51 Divorced women are more likely to experience socioeconomic disadvantages than married women� � 52 Divorced women lose their benefits in terms of health insurance as they are dropped from their husbands' health insurance policies� They also lose their dependent payments and are unable to afford other forms of coverage� Jobless divorced woman find it difficult to pay monthly insurance premiums, so they decide to d...…”
Section: Discussionmentioning
confidence: 99%
“… 36 , 42 , 43 This could have occurred because the health insurance scheme in Indonesia is different from that of other countries. The poorest populations receive subsidized insurance to maintain and increase their health status, 44 such as payment for health services in the emergency department, 45 treatment for chronic illness, 46 and treatment of the factors associated with the success of diabetes mellitus management. 47 The poorest population’s health insurance is fully paid for by the government.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] Only one study showed the data of TC level, but this seems did not provide any insight in assessing the effectivity of PROLANIS in meeting the target of lipid profile in T2DM management. 13 According to a study in Indonesia, primary care physician's adherence to statin prescription was the least among many recommendations in T2DM management. 25 In addition, the regulation does not support the management of LDL in T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, published studies that evaluated the impact of PROLANIS in patients with T2DM are still scarce to this date. [13][14][15][16] Moreover, those studies did not present all the laboratory evaluation data and only used crosssectional method. This study aims to analyze all evaluated clinical parameter outcomes of PROLANIS participants with T2DM treated in a primary healthcare center in Wates, East Java, Indonesia every six month during the first 18-months of PROLANIS implementation.…”
Section: Introductionmentioning
confidence: 99%
“…The poorer, middle, richer, and richest wealth quintiles were less likely to have health insurance than poorest� The previous study stated that there was no significant association between wealth quintile and health insurance� � 41 Another study stated that the richest households were more likely to have health insurance� � 36,42,43 This could have occurred because the health insurance scheme in Indonesia is different from that of other countries� The poorest populations receive subsidized insurance to maintain and increase their health status, , 44 such as payment for health services in the emergency department, , 45 treatment for chronic illness, , 46 and treatment of the factors associated with the success of diabetes mellitus management� � 47 The poorest population's health insurance is fully paid for by the government� The other schemes are paid for by the health insurance members themselves� This scheme makes the poorest populations more likely to be listed as health insurance member, making their coverage rate higher� The ownership of private health insurance may be the reason why the wealthier are less likely to have national health insurance� A study showed that the amount of monthly income as part of wealth is related to the demand for private insurance in Indonesia� � 48 To increase the coverage of health insurance for other economic groups, the government can subsidize premiums for them� The government can work with companies to pass regulations stating that each company has an obligation to pay for that age, education level, wealth quintile, residence, marital status, and earnings type were associated with health insurance coverage� insurance for its workers� This regulation can also protect the health of workers� Rural households are less likely to have health insurance� � 40,43 The primary factor determining coverage for both the subsidized and contributory schemes in Indonesia is that citizens work and are urban residents of Java or Bali� � 49 The affordability of travel to the health insurance office can be another reason for low coverage� The existence of branch offices in each city can increase the reach of insurance agencies� An increase in the number of insurance agencies can make it easier for potential participants to register for NHI� The government can support the spreading of branch offices by providing good infrastructure and communication networks like telephone and internet� The role of the government in providing infrastructure greatly affects the existence of branch offices and customer service� Those who are divorced are less likely to have health insurance� Women often lose their health insurance in the months after a divorce 50 and thus become uninsured� � 51 Divorced women are more likely to experience socioeconomic disadvantages than married women� � 52 Divorced women lose their benefits in terms of health insurance as they are dropped from their husbands' health insurance policies� They also lose their dependent payments a...…”
Section: Discussionmentioning
confidence: 99%